Effect of Austenization and Repeated Quenching on The Microstructures and Mechanical Properties of Wear-Resistant Steel - Nugraha, Yanuar; Mochtar, Myrna Ariati (UI Scholars Hub, 2023)
This study was focused on determining the effect of repeated austenitization and quenching on mechanical properties and microstructure. The experiment was carried out in a rolled quencher facility with a heat treatment process of one to two times, with parameters of an austenizing temperature of 9500C and quenching at a temperature of 8500C with pressurized water media. Testing of specimens, including microstructure observations and hardness testing. The repeated heat treatment process showed an increase in hardness of 0.79% on one-time repeated heat treatment and 1.65% on two repeated heat treatments. This occurs due to the presence accompanied by refinement of the prior austenite grains and the martensite structure. In addition, the hardness value decreases in the surface area 17.9 HV and 24.9 HV due to the deeper accumulation of decarburization 0.06-0.10 mm followed by thicker iron oxide growth 0.04-0.07mm.